EFL high-school teachers’ perceptions of ELT pedagogical reforms and their practice in response to these reforms : - Lê, Thanh Thảo (Trường Đại học Cần Thơ, 2020)
Educational change, particularly English language teaching (ELT) pedagogical reforms, has received much attention from language researchers in the era of globalization and internationalization. Despite many difficulties in the implementation, ELT pedagogical reforms have been widely introduced and adopted in schools all over the world, particularly in Vietnam. The question of what are English foreign language (EFL) teachers’ overall perceptions, understanding, practices in response, and the factors influencing their responses to ELT pedagogical reforms, is the major focus in this study. The study was designed as a mixed-method study, using a questionnaire and interviews as collecting data instruments. The quantitative data were collected from 102 EFL high-school teachers in different high-schools in the Mekong Delta. Among 102 participants, 6 teachers were recruited based on their mean scores of their perceptions of their responses to ELT pedagogical reforms to do the interviews. There are some main following findings. First, the teachers highly perceived ELT pedagogical reforms. Second, they had a high understanding of ELT pedagogical reforms. Third, although the teachers highly supported the reforms, the support did not match with their understanding of the values of the reforms. Fourth, teachers’ responses were strongly influenced by both internal and external factors. Some findings were consistent with and some were different from the findings of the previous research. They both were discussed in this study. Based on the findings, the study suggested some implications to enhance the adoption of ELT pedagogical reforms in Vietnam. Finally, the limitations of this study and the suggestions for further research were also discussed at the end of the thesis.